Mindful parenting di era digital: dampaknya terhadap perkembangan sosial-emosional anak usia dini - Aviska, Shella (Maliki Interdisciplinary Journal, 2026)
The rapid development of digital technology has significantly transformed parenting practices in early childhood. High exposure to digital devices may reduce face-to-face interaction and influence children’s social-emotional development, particularly in emotional regulation, empathy, and social skills. This issue requires a parenting approach that not only focuses on limiting technology use but also strengthens emotional bonding between parents and children. This article presents a conceptual review analyzing the relevance of mindful parenting in the digital era. Drawing on literature related to social-emotional development, parental mediation, and mindful parenting, the article proposes an integrated approach that combines parental awareness in daily interactions with guided digital media use. Such an approach is expected to balance the benefits of technology with children’s developmental needs. Therefore, mindful parenting is positioned as an adaptive foundation for supporting early childhood social-emotional development amid digital transformation.